OPTIMIZATION OF JEPARA POLICE CRIMINAL RESERVE UNITS TO IMPROVE DISCLOSURE OF CORRUPTION CASES IN THE MIDDLE OF THE COVID-19 PANDEMIC: MARIO MICHAEL TAMBUNAN, 18.011, mariotambunan14@gmail.com - Mario Michael TAMBUNAN (Advances in Police Science Research Journal, 2022)
Corruption has become a contagious disease in every apparatus from the lowest level to the highest level. A more comprehensive and holistic effort is needed to carry out an anti-corruption movement at various levels. In addition, the authority of the National Police as an investigation into criminal acts of corruption is regulated according to the laws that apply to police investigators in carrying out their duties and investigations as well as following the Criminal Procedure Code which is specifically regulated in the laws and regulations and Law of the Republic of Indonesia No. 20 of 2001 concerning Amendments to Law No. RI. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption. This study uses interview data collection techniques to obtain primary data and literature study as well as file and situation observations related to the handling of corruption cases from the Jepara Police Criminal Investigation Unit. The Jepara Police Criminal Investigation Unit in corruption cases is still often hampered. This happened as a result of inhibiting factors both externally and internally, there was an unfavorable response from the public, whether reported, other things such as the network of the covid-19 pandemic giving rise to certain stigmas in society making it increasingly difficult to investigate or investigate. the ability of members in case covers should also be improved. The conclusions obtained from the implementation of the investigation process carried out by the investigators of the Jepara Police Criminal Investigation Unit Corruption Unit refer to the Criminal Procedure Code and applicable laws and regulations and become established procedures. Success in conducting investigations into these cases cannot be separated from the leadership and the role of the investigation itself, both in terms of ability and experience.